On the Design and Development of Planar Monopole Antenna for Bone Crack/Void Detection - Ananda Venkatesan Boologam; Kalimuthu Krishnan; Sandeep Kumar Palaniswamy; Sachin Kumar; Shreya Bhowmik; Nivesh Sharma; Deepesh Vaish; Sourish Chatterjee (International Journal of Antennas and Propagation)
In this study, the design of a compact narrowband monopole antenna for bone crack detection is presented. The proposed antenna consists of a modified hexagon-shaped radiator with six triangular slits integrated on its bottom periphery, a rectangular-shaped ground plane, and a microstrip feed line of 50 Ω. The antenna is fabricated on the FR-4 substrate with a thickness of 1.6 mm, an overall size of 32 mm × 30 mm, and electrical dimensions of 0.13λ0 × 0.122λ0, where λ0 is the free space wavelength at 2.45 GHz. The resonant frequency of the designed antenna is 2.45 GHz. The antenna offers a gain of 1.68 dB and an efficiency of 85.3%. The presence of a crack in the bone is detected by observing the shift in the peak resonating frequency of the antenna. This method can detect bone fractures in a noninvasive manner. The human arm model is constructed, and the effect of bone cracks of different lengths on the resonating frequency is investigated. The pig bone and tissues are used to validate the simulated results. The simulated results are in agreement with the measured outcomes. Also, the specific absorption rate (SAR) of the antenna is calculated and found to be less than 0.57 W/kg. The designed monopole antenna has several advantages, including a small footprint, straightforward design, low cost, and easy integration with other devices. The proposed method is suitable for primary-level bone crack diagnosis.